Reactions of dizincocene with sterically demanding bis(iminodi(phenyl) phosphorano)methanes - Schulz, Stephan; Gondzik, Sebastian; Schuchmann, Daniella; Westphal, Ulrich; Dobrzycki, Lukasz; Boese, Roland; Harder, Sjoerd (Chemical Communications, 2010)
Reactions of Cp* Zn with sterically demanding bis(iminodi(phenyl)phosphorano)methanes LH (LH = CH (Ph PNR) (R = Ph L H, SiMe L H, 2,6-i-Pr C H (Dipp) L H) at ambient temperature occurred with elimination of Cp*H and subsequent formation of the homoleptic complex L Zn 1 and the heteroleptic complexes LZnZnCp* (L = L 2, L 3, L 4). 3 is the first structurally characterized heteroleptic organozinc complex with the zinc atoms in the formal oxidation state +1. © The Royal Society of Chemistry.